Estradiol and Estrone Plasma Levels during Application of Three Strengths of a 7-Day Estradiol Transdermal Patch - Setnikar, Ivo; Rovati, Lucio C; Santoro, Antonino; Guillaume, Michel; Mignot, Alain; Renoux, Alain; Gualano, Virginie (Arzneimittelforschung, 1999)
A new estradiol transdermal patch was developed for a once weekly application, with the aim to achieve an optimum practicability and to improve long-term compliance with estrogen replacement therapy. The pharmacokinetics of estradiol (CAS 50-28-2) and of estrone (CAS 53-16-7) during a 7-day application of the new patch is reported in this publication.Unconjugated estradiol and estrone were assayed in plasma in a three-way crossover study on 18 postmenopausal women during and after a 7-day application of 3 strengths of the new patch, with daily release rates of 25, 50 and 75 µg of estradiol.During the 7-day application of the transdermal patches the concentration in plasma of unconjugated estradiol increased from less than 5 pg/ml, typical of postmenopause, to average concentrations of 26, 49 and 66 pg/ml under the patches with the release rates of 25, 50 and 75 µg/day of estradiol, respectively. The increases were linearly related and proportional to the strength of the patches. Upon removal of the patches, the estradiol concentrations returned to the basal postmenopausal values in 8−24 h. Retarded with regard to estradiol, there was also an increase of unconjugated estrone, from basal concentrations of 24 pg/ml to average concentrations of 39, 54 and 62 pg/ml, respectively. Estrone returned to its basal concentrations 24−48 h after removal of the patches. The estradiol/estrone ratio from the low pre-treatment values of 0.15−0.21 typical of postmenopause increased to average values of 0.51, 0.92 and respectively 1.09 during the application of the patches with the three strengths. The ratios are in the range of those of unconjugated hormones during the fertile age of women.The patches were well tolerated by the skin, with rare mild and transient reactions that disappeared spontaneously and did not cause interruption of treatment. Also the systemic tolerability was good, with occasional mild or moderate side effects typical of estradiol found especially under the application of the two higher strengths, i.e. with release of 50 and of 75 µg/day of estradiol.The effective pharmacokinetic performance over the 7-day application, combined with the good general and local tolerability and the need to apply the patches only once weekly confer to the new patches a favorable practicability for the long-term estrogen replacement therapy needed to control the most severe postmenopausal disorders.
Keywords: CAS 50-28-2; CAS 53-16-7; Estradiol, clinical pharmacokinetics, transdermal patch; Estrogen replacement therapy; Estrone, clinical pharmacokinetics